Analisis Evaluasi Kinerja Karyawan Menggunakan Panduan James E Neal Jr - Efrita Norman; Enah Pahlawati; Arman Paramansyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The success of a company is greatly influenced by the performance of employees in the company because if the employee's performance is good, the company's performance will automatically be good and the company will develop and be able to compete with other companies. So the company needs to evaluate the performance of its employees. the fact is that many companies still have difficulty in evaluating employee performance accurately, both in terms of the nature and method of assessment and there are still many agencies or companies in evaluating employee performance there is an imbalance in taking the assessment. The purpose of this study is to analyze employee performance evaluations using guidelines from James E Jr. So that companies can evaluate employee performance properly and correctly and give an impact to the employees themselves. In this study using a qualitative method with a literature study approach where the research authors study the literature published by journals, books, and magazines in this field. The results of this study found that the guide in evaluating the performance of James E Jr. uses indicators, including (1) meeting the standard of achievement accuracy (completing responsibilities and tasks (2) Administration (showing the effectiveness of administration) (3) Effective analysis (4) Able to communicate with other parties (5) Demonstrates ability and quality (6) Can cooperate with others (7) Shows imagination and creative power (8) Able to make decisions and can provide solutions (9) Can delegate (10) Shows communicative nature reliable (11) Improvisation (12) Can present new ideas, methods and approaches (13) Innovation (14) Consider facts and reasons before making an opinion, recommendation or concrete action (15) Understanding of relevant positions and conditions (16) Demonstrate strong authority and capacity to lead (17)Learning (18)Management(19)Motivation (20)Negotiation this approach is more accurate because it looks at all aspects of the employee so that we hope that there will be no more mistakes in evaluating employee performance or at least reducing the error rate in conducting an employee performance evaluation. Keyword : Evaluation, performance, employees